2009
DOI: 10.1038/ejhg.2009.14
|View full text |Cite
|
Sign up to set email alerts
|

16p subtelomeric duplication: a clinically recognizable syndrome

Abstract: We report on two patients with duplication of the subterminal region of chromosome 16p (dup16p) recognized by fluorescent in situ hybridization (FISH) telomere analysis, presenting with closely overlapping facial features and neurological impairment. Distinct facial anomalies included high forehead, sparse eyebrows, blepharophimosis, short nose, everted upper lip, high-arched palate, wide-spaced teeth, and cupped anteverted ears. Susceptibility to vascular anomalies, in particular pulmonary hypertension and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…Many of these subtelomeric deletions or duplications are now recognized as clinically recognizable phenotypes [Holinski-Feder et al, 2000;Battaglia et al, 2008;Digilio et al, 2009]. Partial trisomy 16p is however a rare chromosomal abnormality characterized by ID and multiple congenital abnormalities (MCA) [Leonard et al, 1992;Schinzel et al, 1997;Tschernigg et al, 2002;Sommer et al, 2006;Digilio et al, 2009]. Some authors had reported that a duplicated segment within 16p13 is responsible for the clinical manifestations of this disorder and likely the critical region [Schinzel et al, 1997;Tschernigg et al, 2002;Sommer et al, 2006;Digilio et al, 2009].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Many of these subtelomeric deletions or duplications are now recognized as clinically recognizable phenotypes [Holinski-Feder et al, 2000;Battaglia et al, 2008;Digilio et al, 2009]. Partial trisomy 16p is however a rare chromosomal abnormality characterized by ID and multiple congenital abnormalities (MCA) [Leonard et al, 1992;Schinzel et al, 1997;Tschernigg et al, 2002;Sommer et al, 2006;Digilio et al, 2009]. Some authors had reported that a duplicated segment within 16p13 is responsible for the clinical manifestations of this disorder and likely the critical region [Schinzel et al, 1997;Tschernigg et al, 2002;Sommer et al, 2006;Digilio et al, 2009].…”
Section: Introductionmentioning
confidence: 96%
“…Duplication of 16p13.3 (RubinsteinTaybi syndrome region) also can cause a recognizable syndrome with mild to moderate ID, dysmorphic features, hand and foot anomalies as well as congenital heart defects in some cases [Marangi et al, 2008;Digilio et al, 2009;Thienpont et al, 2010;Chen et al, 2012].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Terminal duplications of 16p that have been reported include 33 reports on 16p13.3 duplications and 100 reports on 16p13.11 duplications and these have been well described 1, 3…”
Section: Introductionmentioning
confidence: 99%